Predicting and Monitoring Air and Weather Quality Index Using Machine Learning - Divya.J , Anitha K, Chandima, M,Dharshini V (International Journal of Modern Agriculture, 2020)
Many plants suffer everyday because of abnormal weather conditions. Here, we deploy an idea to predict and monitor the air and weather quality, and to give some notifications about the air and weather quality along with some plant suggestions beforehand itself. This idea will help the farmer to know about the weather before, accordingly they can plan their work for that day. The system leverages Machine learning and Deep learning helps improving the accuracy of the output. The previous year data are collected, by using that data we will be predicting various parameters like air quality for the next few days/hours. This information about the prediction will be displayed in a GUI interface along with suitable crop for that